Integrated resort development: The case of Cavo Sidero, Crete - Andriotis, Konstantinos (My University, 2008)
Many governments have encouraged integrated resort development in an attempt to improve the well-being of the local population by generating jobs and increasing income, and because of the easier control of tourism activities within their boundaries. However, most research reports various adverse environmental and social impacts. Because of the difficulty of assessing the impacts that may result from the construction of integrated resorts, the majority of research has been conducted after their construction. This study is an impact assessment carried out prior to a large-scale development that examines whether an integrated resort proposed for development at Cavo Sidero, Crete, will result in positive impacts for the destination and the local community, and it investigates whether any conflicting interests have arisen within stakeholder groups. Through primary research examining various stakeholder groups it is revealed that economic impacts are perceived as mostly positive, while social and environmental impacts, in many cases, are viewed as negative, and that conflicting interests have arisen between different stakeholder groups.
Keywords: Conflicting interests; Crete; Impacts; Integrated resorts; Large-scale developments; Perceptions